2017
DOI: 10.1123/jsr.2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

Balance Training Versus Balance Training With STARS in Patients With Chronic Ankle Instability: A Randomized Controlled Trial

Abstract: While statistically no more effective, exceeding minimal detectable change scores and favorable effect sizes suggest that a 4-week progressive BTS program may be more effective at improving self-assessed disability and postural control in CAI patients than balance training in isolation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 0 publications
4
51
0
Order By: Relevance
“…For example, improvements were noted after 4-week interventions that included hop-stabilization exercises. 14,15,19 Additionally, the magnitude of the improvements we found were consistent with, if not larger than, those reported previously. The magnitudes of improvement on the FAAM and FAAM-S were also larger than previously established 22 minimal clinically important difference scores (8% and 9%, respectively) for these questionnaires in patients with CAI.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For example, improvements were noted after 4-week interventions that included hop-stabilization exercises. 14,15,19 Additionally, the magnitude of the improvements we found were consistent with, if not larger than, those reported previously. The magnitudes of improvement on the FAAM and FAAM-S were also larger than previously established 22 minimal clinically important difference scores (8% and 9%, respectively) for these questionnaires in patients with CAI.…”
Section: Discussionsupporting
confidence: 92%
“…These impairments decrease the adaptability for coordinating movements during changing task and environmental demands, resulting in a continuum of disability. 29 Research 11,14,15,17 has consistently shown that coordination training improved a variety of outcomes in those with CAI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Impaired balance in patients with CAI can be improved after balance training. 6,[15][16][17] Whereas multiple balancetraining programs have been developed, researchers have recommended that the sensorimotor system be progressively challenged to develop motor ''solutions'' to new motor ''problems'' by increasing the difficulty of motor tasks after movement proficiency is demonstrated. 15,18 Progressively increasing the difficulty of hopping and balance exercises may be beneficial, as it may allow the sensorimotor system time to adapt to more challenging tasks.…”
mentioning
confidence: 99%
“…13,14 Similarly, combining balance training with STARS may further enhance the individual benefits of both treatments as highlighted in a preliminary investigation. 31 …”
Section: Discussionmentioning
confidence: 99%